Inherent Safety Cost Index (Isci) For Preliminary Process Design - Nur Hidayah bt Mansor, Nur Hidayah (Universiti Teknologi Petronas, 2010)
Inherent safety principles were first introduced by Trevor Kletz in 1976 after Flixborough accident. The inherent safety principles include minimization, substitution, attenuation, simplification, and limiting of. Implementing inherent safety in the design aims at selecting and designing the process to eliminate hazards, in contrary to passive control which accepts the hazards and implementing add-on systems to control them. Inherent safety is best considered in the initial stages of the design when fundamentals decisions which have a large impact on inherent safety are made. There are a few established models developed for inherent safety index but most of them only consider process safety. At present, the only index established which includes cost evaluation is Integrated Inherent Safety Index (I2SI). The costs to operate a plant which is built based on inherent safety principles is proven to be more economically by several writers. The project will require the application of inherent safety principles in the preliminary design which will consequently reduce the cost of losses as the probability of accident occurrence will be reduced.